Distribution of uterocervical angles of pregnant women at 16+ 0 to 23+ 6 weeks gestation with low risk for preterm birth: first vietnamese cohort of women with singleton pregnancies - Thi Hoang Trang Nguyen; Van Tam Vu; Vu Quoc Huy Nguyen (BMC, 2023)
Abstract Background Cervical length (CL) measured by ultrasound in the second trimester is a predictor of spontaneous preterm birth (sPTB). The uterocervical angle (UCA) has recently been suggested as a predictor to identify women at risk of sPTB. The aim of this study was to investigate the UCAs' distribution in singleton pregnant women at 16+ 0 − 23+ 6 weeks of gestation with low risk for sPTB. Methods This was a prospective cohort study of 1,051 pregnant women with singleton pregnancies at low risk for preterm delivery. Pregnant women with a viable singleton fetus at 16+ 0 − 23+ 6 weeks of gestation were enrolled in the study conducted at the Haiphong Hospital of Obstetrics and Gynecology, Vietnam, from 09/2019 to 09/2020. CL and the UCA were assessed using transvaginal ultrasonography (TVS) by a single sonographer. Subjects were followed-up until the end of pregnancy, and maternal and neonatal outcomes were recorded. The UCAs' range and their relationship with gestational age were evaluated using regression analysis. P < 0.05 was considered statistically significant. Results The normal range of the UCA (5th − 95th percentiles) was 46.47° (95% CI, 40.27°-51.81°) to 127.06° (95% CI, 123.02° − 130.71°). The UCAs in the preterm birth (< 37 weeks) and full-term groups were 117.86° ± 20.25° and 83.80° ± 24.18°, respectively (p < 0.001). Linear regression analysis showed a significant change in the UCA range from 16+ 0 to 23+ 6 weeks of gestation (2.51 degrees per week, p < 0.001). The linear function yielded the highest correlation coefficient in the variation rule of the UCA values (r = 0.22). A total of 42/63 (66.7%) patients with preterm birth < 37 weeks had a UCA above the 75th percentile. The majority of women with preterm birth had a UCA ≥ 95° compared with those with full-term delivery (88.9% vs. 31.3%, p < 0.001). Conclusions The results of this study present background information about the normal range of UCA values in singleton pregnant women at 16+ 0 to 23+ 6 weeks at low risk for sPTB in this Vietnamese cohort. In this study population at low risk for sPTB, pregnant women with a UCA value ≥ 95o were also considered at risk for preterm birth.